Assessing the Character of Pancasila Student Profiles: Challenges Encountered by Teachers - Medita Ayu Wulandari; Siti Ruqoyyah; Cucun Sutinah; Arie Rakhmat Riyadi (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractAdministering assessment is essential in education, including, in the implementation of character building in the Pancasila Student Profiles. This study was conducted to examine the implementation of the P5 (the Project for Strengthening Pancasila Student Profiles) in primary schools and the challenges teachers encountered in assessing the P5 character. Descriptive analysis was used in this study. Data collection was carried out using questionnaires and interviews given to 160 teachers representing 160 schools in 16 sub-districts in West Bandung, Indonesia. The results of the data analysis show that several elements are dominantly used from each dimension. Particularly noteworthy is that the creativity dimension is rarely taught. In terms of assessments, summative assessment is the most frequently practiced assessment among teachers. The number of teachers who carried out diagnostic and formative assessments is relatively small (<5%). Furthermore, the challenges or difficulties faced by the teachers in preparing the assessment encompass aspects such as the P5 comprehension, how to cultivate the P5 character, the main obstacles in instilling the P5 character, and measuring the P5 character.Keywords: character education, assessment, primary teachers, Project to Strengthen the Pancasila Student Profiles (P5), Merdeka curriculum.Â AbstrakPelaksanaan kegiatan asesmen di sekolah merupakan suatu hal yang penting untuk dilakukan. Begitupun halnya pada pelaksanaan pembelajaran karakter Profil Pelajar Pancasila. Penelitian ini dilakukan untuk memberikan gambaran pelaksanaan asesmen dalam Projek Penguatan Profil Pelajar Pancasila di sekolah dasar dan kesulitan apa saja yang dihadapi guru dalam mempersiapkan dan melaksanakannya. Analisis deskriptif digunakan dalam penelitian ini. Pengumpulan data dilakukan dengan menggunakan angket dan wawancara yang diberikan kepada 160 guru terbaik yang mewakili 160 sekolah di 16 kecamatan di kabupaten Bandung Barat, Indonesia. Hasil analisis data menunjukkan bahwa dari setiap elemen terdapat beberapa elemen yang dominan digunakan; hal yang paling mencolok adalah adanya salah satu dimensi yang tingkat pengajarannya masih rendah yaitu kreativitas. Kemudian dalam pelaksanaan penilaian, kegiatan yang paling sering dilakukan guru adalah penilaian sumatif. Jumlah guru yang melaksanakan penilaian diagnostik dan formatif masih sedikit (<5%). Selanjutnya kesulitan yang dihadapi guru dalam mempersiapkan evaluasi itu sendiri terbagi dalam beberapa kategori, seperti pemahaman P5, cara menumbuhkan karakter P5, kendala utama dalam menanamkan karakter P5 dan mengukur karakter P5.Kata kunci: pendidikan karakter, asesmen, guru sekolah dasar, projek penguatan profil pelajar pancasila (P5), kurikulum merdeka.